Network disruption detected in TH (Thailand) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Thailand. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: TH-2026-0001. Severity: critical. Confidence: 75%